Ataxia plus myoclonus in a 23-year-old patient due to STUB1 mutations - Córdoba, Marta (2014)
More than 1,000 mutations mapping to 60 different loci have been recognized as the cause of hereditary ataxias. However, almost 50% of the cases are still genetically uncharacterized, with etiology remaining to be identified.1 Diagnosis and research in rare diseases such as ataxia has been significantly improved with the recent availability of next generation sequencing technologies.2 In order to expand the phenotype recently described in ataxia due to STUB1 mutations and to illustrate the utility of clinical genomics in the diagnosis of ataxias, we present a 23-year-old patient who had ataxia plus myoclonus in whom exome sequencing revealed novel compound heterozygous mutations in the STUB1 gene.